Experimental Evolution of the Thermal Performance Curve - Zilio, Giacomo; Moodie, Iain R ; 0000-0003-3416-1198; Malusare, Sarthak P.; Devillez, Marie-Ange; Givens, Justina; Gougat-Barbera, Claire; Fronhofer, Emanuel A. (bioRxiv, 2025)
The thermal performance curve (TPC) of an organism captures how population growth depends on temperature. When populations experience increased temperatures, such as during global climate change, one prediction is that their TPC can evolve to accommodate the new environmental temperature. Although studies on TPC evolution have mostly focused on modifications in population growth rates, TPC evolution can be strongly trait-dependent and require a multi-trait analysis. Thus, if and how the entire TPC across a multitude of traits evolves to change its shape in response to increased temperatures remains debated. Here, we empirically tested how the TPCs of multiple demographic, life-history and movement traits can evolve by selecting four freshwater protist species at increased temperatures starting from clonal populations. After one year of selection, populations showed a signature of evolutionary responses to the highest selection temperatures in different traits depending on the species. Particularly, we found consistent evolutionary reductions in body size in the three species having the largest cells and evolved changes in movement behaviour in all species. In contrast, we overall observed little modifications in population growth rate and in the corresponding TPC shape. These results suggest that adaptation, via evolution of TPCs, might involve the concurrent evolution of several traits. However, this may be species-specific and difficult from de-novo mutation alone, suggesting that natural populations that do not have sufficient standing genetic variation might have to be reliant on other means of mitigating the effects of climate change, such as dispersal.
Keywords: thermal niche; experimental evolution; climate change; global change; adaptation